The Chaffey story - Green, Lyall, 1915- (1962)
History of Chaffey family of Tamworth.
Manuscript reference no. : NLA MS 6394.
Photocopy.
Original in private ownership.
Keywords: Chaffey family; Tamworth (N.S.W.) -- Genealogy